Predictive ability of the 2002 and 2010 versions of the Tumour‐Node‐Metastasis classification system regarding metastasis‐free, cancer‐specific and overall survival in a European renal cell carcinoma single‐centre series. (26th October 2012) - Pichler, Martin; Hutterer, Georg C.; Chromecki, Thomas F.; Jesche, Johanna; Kampel‐Kettner, Karin; Groselj‐Strele, Andrea; Pummer, Karl; Zigeuner, Richard
Abstract : What's known on the subject? and What does the study add? As different and heterogenous populations of patients with RCC can be found in different geographic regions, newly proposed cancer staging systems need an independent validation of their clinical usefulness and prognostic significance. Only a few published studies have compared the 'old' 2002 version of the TNM classification system for RCC with the recent 2010 version, all of them using cancer‐specific survival as their endpoint, and controversial results were reported regarding the potential superiority of the 2010 version over the 2002 version of this cancer staging system. The aim of the study was to validate and compare the predictive ability of the 2010 with the 2002 version of the TNM classification system regarding metastasis‐free, overall and cancer‐specific survival in a large central European cohort of patients with RCC. According to our data, the predictive ability of the 2010 version of the TNM classification system regarding the evaluated endpoints is not superior to the 2002 version. OBJECTIVE: To compare the predictive ability of the Tumour‐Node‐Metastasis (TNM) classification systems for renal cell carcinoma (RCC) using three different endpoints: metastasis‐free (MFS); overall (OS); and cancer‐specific survival (CSS). PATIENTS AND METHODS: Data from 2739 consecutive patients with RCC, who underwent surgery at a single academic centre, were evaluated using multivariate Cox proportional models, Harrell's concordance (c)‐index and by applying decision curve analysis (DCA) with regard to MFS, OS and CSS. RESULTS: According to TNM 2010, significant differences for MFS were observed for pT1a vs pT1b, pT1b vs pT2a, pT3a vs pT3b and pT3b vs pT3c stages, respectively (all P < 0.05). With regard to OS, significant differences could be observed in pT1a vs pT1b and pT3a vs pT3b stages, respectively (all P < 0.05). The c‐index for CSS, OS and MFS was slightly higher for the 2002 than for the 2010 version of the TNM classification system. Non‐inferiority of the 2002 TNM system is supported by the results of the DCA. CONCLUSION: According to our data, the predictive ability of the 2010 version of the TNM classification system regarding three different clinical endpoints is not superior to the 2002 version of this staging system.